Citizen police academies: Observing goals, objectives, and recent trends - Bumphus, Vic W. (American journal of criminal justice, 1999)
The American police establishment is concentrating on a number of citizen-based tactics in an attempt to embrace the principles of community policing. One approach receiving widespread attention is the Citizen Police Academy. The idea of a Citizen Police Academy is being adopted at a phenomenal rate by a variety of law enforcement agencies. Administrators assume that the Citizen Police Academy is an effective technique for interacting with community members. The present research verifies the growth in this area and provides the first major descriptive analysis of this phenomenon.